Modeling of separated flows near a suction slot - Logachev, I.N.; Logachev, K.I.; Zorya, V.Yu.; Averkova, O.A. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2010)
Regularities of velocity distribution at the suction slot opening are determined experimentally, analytically, and numerically. A dependence of the local drag coefficient, the stalling velocity, and the line of separated flow on the length of the screen located at the slot inlet is found. The work was supported by the Russian Foundation for Basic Research (project 08-08-13687-ofi_c) and the Fulbright International Exchange Program.